University students’ self-assessment of data literacy: A validation study - Jeonghyun Kim; Lingzi Hong; Ayoung Yoon (PLoS ONE, 2025)
As data literacy has emerged as a critical skill for professionals across industries, educators in higher education have incorporated it into their curricula and instruction. Understanding and evaluating the factors that shape an individual’s data literacy is important for benchmarking proficiency and tailoring curricula, yet the underlying components and structure of data literacy for students in four-year institutions are unknown. This study validated the Data Literacy Self-Efficacy Scale (DLSES) with 1,816 students enrolled in two four-year institutions. Exploratory and confirmatory factor analyses were conducted to determine the construct of the scale, and the item analysis was used to address the validity of the items on the scale. The exploratory factor analysis identified eight distinct factors comprising 29 items. The results of confirmatory factor analysis showed a good model fit, CFI = 0.994, TLI = 0.994, RMSEA = 0.053, SRMR = 0.044. This study demonstrated the 29-item refined version of the DLSES to be a reliable and valid tool for measuring individuals’ self-efficacy levels for data literacy. Furthermore, the scale could form the basis for curriculum development and help educators design targeted interventions that address specific learning needs.